Pelatihan Kesehatan Reproduksi Untuk Meningkatkan Komunikasi Efektif Orang Tua Kepada Anak - Nirma Yullidya (Jurnal Psikologi Tabularasa, 2015)
This study aims to determine the effect of reproductive health training on improving the effective communication skills of parents to children. Subjects of this study consist of 12 parents as experimental group and 12 parents as control group. The experimental design used was Pretest-Posttest Control Group Design using Mann-Whitney U Test and Wilcoxon Signed Ranks Test for data analysis method. The result showed that there was no significant difference between the experimental group and control group with p 0.05, and it showed that there was a significant difference between posttest result of experimental group and control group after experimental group treatment with p 0.05. It also showed that there is a significant difference between the pretest and posttest results of the experimental group with p 0.05. Based on the above results, reproductive health training can improve the effective communication of parents to children.